Rubber composition, method for continuously preparing master batch by adopting rubber composition and application of prepared master batch
By using zinc-free vulcanization additives in heavy-duty tire rubber, the problem of environmental pollution in zinc in heavy-duty tires is solved, and the performance and environmental protection of the rubber material are improved, and zinc-free emissions are achieved and efficient preparation of glue.
Patent Information
- Application Number
- CN202411329034.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The zinc contained in heavy-load tires has environmental pollution, and the traditional tire rubber compound mixing process consumes high energy, has large dust pollution, and poor filler dispersion, which affects the performance of the rubber.
Using a rubber composition, including rubber, filler, zinc-free vulcanization additive and other additives, the zinc-free vulcanization additive is prepared by pre-reacting anti-aging agent and vulcanization system medicine under the catalytic action of stearic acid. , used for continuous preparation of masterbatch.
It has achieved zinc-free emissions, and achieved cross-linking density and rubber properties close to that of zinc-containing rubber compositions. It is especially suitable for the preparation of heavy-duty tires. It has excellent tensile, tear and other properties, and can adapt to harsh working environments.
Smart Images

Figure BDA0005056502100000021 
Figure BDA0005056502100000041 
Figure BDA0005056502100000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tread rubber preparation, and in particular to a rubber composition, a method for continuously preparing a masterbatch using the same, and application of the prepared masterbatch. Background Art
[0002] The working environment of heavy-duty tires is harsh. The road surface is uneven and there are sharp gravel and other debris. They are greatly impacted by hard objects. In addition, the thickness of each part of the tire body is large. The heat generated during driving is difficult to dissipate, and the temperature rises rapidly. The tires are prone to excessive wear, cuts, punctures, chipping, and thermal peeling, which seriously affect the service life of heavy-duty tires. The traditional tire rubber mixing process is energy-consuming, time-consuming, and dust-prone, and the filler dispersion is poor. Increasing the amount of filler is a common means to improve the wear resistance of the rubber. Increasing the amount of filler will inevitably increase the energy consumption during the mixing process, generate more heat during mixing, and the rubber molecules are subjected to strong shear at high temperatures, which is easy to be plasticized, affecting the tensile and tearing properties of the rubber. Highly filled rubber usually has a higher hysteresis loss factor and heat generation.
[0003] In recent decades, wet mixing (liquid phase mixing) technology has developed rapidly, which can reduce the number of mixing stages, reduce energy consumption, avoid dust pollution, and solve the problem that high specific surface area fillers are difficult to disperse in conventional mixing. However, most wet mixing technologies use latex and filler slurry, and then produce masterbatch by chemical coagulation. CN106750389 A discloses a method for preparing white carbon black / solution polymerized styrene butadiene rubber masterbatch by wet method, firstly dispersing white carbon black in an organic solvent, adding a silane coupling agent to modify the white carbon black, and then mixing it with the solution polymerized styrene butadiene rubber solution, and removing the organic solvent by co-evaporation of water vapor and solvent to obtain white carbon black / solution polymerized styrene butadiene rubber masterbatch. However, the dehydration time is long, and it is only applied to white carbon black and solution polymerized styrene butadiene rubber system. "Application of Liquid-phase Mixed NR / Carbon Black Composites in Tread Rubber" (Tire Industry, 2005, 25(2):4) discloses the application of carbon black composites (CEC). The carbon black composites are prepared by Cabot Corporation of the United States using natural rubber latex and carbon black slurry in a liquid phase continuous process for manufacturing natural rubber carbon black masterbatch. This method of preparing rubber filler masterbatch by liquid phase continuous mixing simplifies the mixing process and mixing time, reduces energy consumption and labor, but the types and contents of rubber and fillers used in the preparation of the masterbatch are limited, and additives such as masterbatch chemicals still need to be added during the tread rubber mixing process.
[0004] On the other hand, zinc oxide in tire debris enters the water circulation system and has been proven to cause environmental water pollution. The European Commission Directive 2400 / 73 / EC and the SB1260 bill proposed by California in 2016 both recommend limiting the use of zinc or zinc oxide in tires. Companies in the rubber tire industry are facing pressure to transform to a green environment and are committed to reducing the impact of the production process on the environment. Summary of the invention
[0005] The main purpose of the present invention is to provide a rubber composition, a method for continuously preparing a masterbatch using the same and application of the prepared masterbatch, so as to solve the problem of environmental pollution caused by zinc contained in heavy-load tires in the prior art.
[0006] In order to achieve the above-mentioned object, according to one aspect of the present invention, a rubber composition is provided, which comprises, by weight, 100 parts of rubber, 30 to 100 parts of filler, 5 to 15 parts of zinc-free vulcanization accelerator and 5 to 30 parts of other accelerators; wherein the zinc-free vulcanization accelerator is prepared by pre-reacting an antioxidant with a vulcanization system chemical under the action of a catalyst, and the catalyst comprises stearic acid.
[0007] Furthermore, the reaction temperature of the pre-reaction is 100-190°C, and the reaction time is 1min-120min; the preferred reaction temperature is 110-170°C, and the reaction time is 5min-50min;
[0008] Preferably, 0.5 to 15 phr of stearic acid, 0.5 to 15 phr of antioxidant, and 0.5 to 15 phr of vulcanization system chemicals are added in the pre-reaction;
[0009] Preferably, a first solvent is further added in the pre-reaction, and the first solvent is any one or more of butanol, octanol, N-methylpyrrolidone, octane, nonane, decane, toluene, and xylene;
[0010] Optionally, the catalyst further comprises 1 to 10 phr of zinc oxide, and after the pre-reaction is completed, the zinc oxide is filtered out.
[0011] Further, the vulcanization system chemicals include any one or more of a vulcanizing agent and an accelerator, the accelerator includes any one or more of a sulfonamide vulcanization accelerator, a sulfenamide vulcanization accelerator and a thiazole vulcanization accelerator, preferably, the accelerator is selected from any one or more of CZ, DZ, DM, M and NS;
[0012] and / or, the antioxidant is a p-phenylenediamine antioxidant,
[0013] Preferably, the antioxidant is selected from any one or more of 4020 (6PPD), 4010NA (IPPD) and 7PPD;
[0014] Preferably, the antioxidant is a compound having a structure of formula I:
[0015]
[0016] In Formula I, R 1 Selected from C1-C 18Chain hydrocarbon groups, C3-C 18 Alicyclic hydrocarbon or C6-C 18 The aromatic hydrocarbon group, R 2 , R 3 , R 4 , R 5 Selected from C1-C 18 The chain hydrocarbon group, R 2 With R 3 or R 4 With R 5 They can also form aliphatic rings separately or simultaneously, R 6 Selected from H, C1-C 18 Chain hydrocarbon groups, C3-C 18 Alicyclic hydrocarbon or C6-C 18 x=0 or 1, y=0 or 1, z=0 or 1, w=0 or 1, and at least one of x and w has a value of 1, and at least one of y and z has a value of 1.
[0017] Further, the filler is selected from any one or more of carbon black and white carbon black;
[0018] Preferably, the specific surface area of white carbon black is 10 to 500 m 2 / g, more preferably 10 to 300 m 2 / g, more preferably 100 to 300 m 2 / g;
[0019] Preferably, the oil absorption value of white carbon black is 20 to 350 mL / 100 g, more preferably 25 to 300 mL / 100 g, and further preferably 30 to 290 mL / 100 g;
[0020] Preferably, the specific surface area of carbon black is 10 to 500 m 2 / g, more preferably 10 to 300 m 2 / g, more preferably 100 to 300 m 2 / g.
[0021] Further, the rubber is selected from any one or more of natural rubber, polyisoprene rubber, molten polystyrene-butadiene rubber, latex polystyrene-butadiene rubber and polybutadiene rubber;
[0022] Preferably, the molecular weight of the rubber is 1,000 to 40 million, more preferably 5,000 to 30 million, and even more preferably 10,000 to 8 million.
[0023] Further, other additives include any one or more of oil, antioxidant, coupling agent, activator, antioxidant, heat stabilizer, light stabilizer, flame retardant, dye, pigment, plasticizer, softener, processing aid, vulcanizer and accelerator;
[0024] Preferably, the coupling agent includes any one or more of bis(triethoxypropylsilane)tetrasulfide and disulfide, 3-thiocyanatopropyl-triethoxysilane, γ-mercaptopropyl-trimethoxysilane, zirconate coupling agent, phthalate coupling agent and nitro coupling agent;
[0025] Preferably, the softener includes any one or more of aromatic oil, tackifying resin and anti-tearing resin.
[0026] In order to achieve the above object, according to one aspect of the present invention, there is provided a method for continuously preparing a masterbatch using any of the above-mentioned rubber compositions, the method comprising: step S1, mixing a filler, a zinc-free vulcanizing agent, other additives, a rubber and a second solvent, and forming a mixture by stirring; step S2, separating the solvent from the mixture to obtain a masterbatch.
[0027] Furthermore, the solvent separation includes any one of separating the solvent by evaporation, separating the solvent by low-pressure vacuum drying, separating the solvent by heating, separating the solvent by spray drying, separating the solvent by expansion drying and separating the solvent by flash evaporation;
[0028] Preferably, after step S2, the method further comprises step S3 of drying the masterbatch, wherein the drying is performed by heating and / or mechanical drying.
[0029] Further, the second solvent is selected from any one or more of aliphatic hydrocarbon solvents, aromatic hydrocarbon solvents, chlorinated hydrocarbon solvents, ketone solvents, ether solvents and ester solvents;
[0030] Preferably, step S1 comprises mixing the rubber and the second solvent to prepare a rubber solution, and then mixing the rubber solution with a filler, a zinc-free vulcanizing agent, and other additives;
[0031] Preferably, the concentration of rubber in the rubber solution is 1% to 60% by weight, more preferably 5% to 40% by weight, and even more preferably 10% to 30% by weight.
[0032] According to another aspect of the present invention, there is provided a use of a masterbatch prepared by any one of the above methods in a heavy-load tire.
[0033] By applying the technical solution of the present invention, a zinc-free vulcanization accelerator is used in the rubber composition. The zinc-free vulcanization accelerator reacts the antioxidant and the vulcanization system medicine under the catalytic action of stearic acid to generate an active intermediate. The active intermediate has the function of promoting vulcanization and can activate the accelerator in advance, so that the active intermediate can replace the function of zinc oxide. The rubber composition does not contain zinc element, can achieve zinc-free emission, and is environmentally friendly; and the vulcanization accelerator can enable the rubber composition to obtain a crosslinking density close to that of a zinc-containing rubber composition without zinc, and rubber properties such as hardness, tensile stress and hysteresis, especially suitable for the preparation of heavy-duty tires, with excellent tensile and tearing properties, and can adapt to harsh working environments. DETAILED DESCRIPTION
[0034] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0035] As analyzed in the background technology of this application, due to the harsh working environment of heavy-duty tires, higher requirements are put forward for rubber materials than ordinary tires, and the zinc contained in the heavy-duty tires in the prior art has the problem of environmental pollution. On this basis, this application provides a rubber composition, a method for continuously preparing a masterbatch using the same, and the application of the prepared masterbatch.
[0036] According to a typical embodiment of the present application, a rubber composition is provided, characterized in that, in parts by weight, the rubber composition comprises: 100 parts of rubber, 30 to 100 parts of filler, 5 to 15 parts of zinc-free vulcanization aids and 5 to 30 parts of other additives; wherein the zinc-free vulcanization aid is prepared by pre-reacting an antioxidant with a vulcanization system drug under the action of a catalyst, and the catalyst comprises stearic acid.
[0037] The above-mentioned rubber composition adopts a zinc-free vulcanization accelerator, which reacts an antioxidant with a vulcanization system drug under the catalytic action of stearic acid to generate an active intermediate, which has the function of promoting vulcanization and plays the role of an early activation accelerator, so that the active intermediate can replace the role of zinc oxide. The rubber composition does not contain zinc element, can achieve zinc-free emission, and is environmentally friendly; and the vulcanization accelerator can enable the above-mentioned rubber composition to obtain a crosslinking density close to that of a zinc-containing rubber composition without zinc, and rubber properties such as hardness, tensile stress and hysteresis, especially suitable for the preparation of heavy-duty tires, with excellent tensile and tearing properties, and can adapt to harsh working environments.
[0038] Taking the phenylenediamine antioxidant and 2-thiobenzothiazole vulcanization system chemicals as an example, the reaction occurring in the pre-reaction is shown in the following reaction equation, and the generated active intermediate has the effect of promoting vulcanization.
[0039]
[0040] In order to further increase the content of active intermediates in the zinc-free vulcanization aid, in some embodiments of the present application, the reaction temperature of the above-mentioned pre-reaction is 100-190°C, and the reaction time is 1min-120min; the preferred reaction temperature is 110-170°C, and the reaction time is 5min-50min. The obtained zinc-free vulcanization aid has a better effect of promoting cross-linking, and the tire prepared by the rubber composition containing it has better comprehensive performance.
[0041] In some preferred embodiments of the present application, 0.5 to 15 phr of stearic acid, 0.5 to 15 phr of antioxidant, and 0.5 to 15 phr of vulcanization system chemicals are added in the pre-reaction, the reaction efficiency is high, and it is beneficial to exert the synergistic effect of the zinc-free vulcanization aid formed by the above components in the rubber composition.
[0042] In some embodiments of the present application, the first solvent is further added to the pre-reaction so that the antioxidant, the vulcanization system drugs and the catalyst are evenly dispersed, and the activation of the prepared zinc-free vulcanization aid is further improved. The first solvent in the pre-reaction can dissolve the stearic acid, antioxidant, and vulcanization system drugs involved in the pre-reaction, and has no adverse effect on the reaction of the antioxidant and the vulcanization system drugs, and can be selected in the prior art. The amount of solvent added can be adjusted according to its solubility for the above-mentioned pre-reaction raw materials.
[0043] Preferably, the first solvent is any one or more of butanol, octanol, N-methylpyrrolidone, octane, nonane, decane, toluene and xylene. These solvents not only have good solubility for stearic acid, antioxidants and vulcanization system chemicals, but also are conducive to the pre-reaction and improve the reaction efficiency.
[0044] The first solvent added in the preliminary reaction can be removed after the reaction is completed, or the product system containing the solvent, i.e., the zinc-free vulcanizing agent solution, can be used as part of the rubber composition and directly used in the subsequent continuous preparation of the masterbatch and directly mixed with the rubber solution.
[0045] In some embodiments of the present application, the catalyst also includes 1 to 10 phr of zinc oxide. After the pre-reaction is completed, the zinc oxide is filtered out. Through the co-catalysis of zinc oxide and stearic acid, more active intermediates can be generated in the pre-reaction, so that the rubber composition has better performance. In addition, since the zinc oxide is still solid in the above-mentioned first solvent, the zinc oxide in the pre-reaction solution system can be filtered out to achieve zinc-free and high-performance rubber composition.
[0046] In some embodiments of the present application, the above-mentioned vulcanization system chemicals include any one or more of vulcanizers and accelerators. Preferably, the above-mentioned vulcanization system chemicals contain accelerators, and the vulcanizers are added during the preparation of rubber products. The accelerators include any one or more of sulfonamide vulcanization accelerators, sulfenamide vulcanization accelerators, and thiazole vulcanization accelerators. Preferably, the accelerators are selected from any one or more of CZ, DZ, DM, M, and NS.
[0047] In some embodiments of the present application, the antioxidant is a paraphenylenediamine antioxidant, such as any one or more of 4020 (6PPD), 4010NA (IPPD) and 7PPD.
[0048] In some preferred embodiments of the present application, the antioxidant is a compound having a structure of Formula I:
[0049]
[0050] In Formula I, R 1 Selected from C1-C 18 Chain hydrocarbon groups, C3-C 18 Alicyclic hydrocarbon or C6-C 18 The aromatic hydrocarbon group, R 2 , R 3 , R 4 , R 5 Selected from C1-C 18 The chain hydrocarbon group, R 2 With R 3 or R 4 With R 5 They can also form aliphatic rings separately or simultaneously, R 6 Selected from H, C1-C 18 Chain hydrocarbon groups, C3-C 18 Alicyclic hydrocarbon or C6-C 18 x=0 or 1, y=0 or 1, z=0 or 1, w=0 or 1, and at least one of x and w has a value of 1, and at least one of y and z has a value of 1.
[0051] When the antioxidant added in the above-mentioned pre-reaction is a p-phenylenediamine antioxidant of the above-mentioned formula I, it not only has a better effect but is also more environmentally friendly.
[0052] In some embodiments of the present application, the zinc-free vulcanizing accelerator may also be a masterbatch type vulcanizing accelerator, that is, the product after the pre-reaction is mixed with the rubber, and preferably, the amount of rubber added is 0 to 150 phr. In the preparation process of the masterbatch type zinc-free vulcanizing accelerator, if the first solvent is added in the pre-reaction, the first solvent of the pre-reaction system may be removed first and then mixed with the rubber, or may be directly mixed with the rubber, and the solvent may be removed after mixing, or may not be removed and directly used in the subsequent process.
[0053] The rubber included in the above-mentioned zinc-free vulcanization aid can be any one or more of natural polymers or synthetic polymers. Preferably, the rubber is selected from any one or more of natural rubber, styrene-butadiene rubber, isoprene rubber, natural eucommia gum, polyisoprene rubber, butadiene rubber, halogenated butyl rubber and EPDM rubber; preferably, the molecular weight of the rubber is 1,000 to 40 million, more preferably 5,000 to 30 million, and more preferably 10,000 to 8 million.
[0054] It should be noted that when the zinc-free vulcanizing accelerator is a masterbatch type accelerator, the rubber composition contains 100 parts of rubber and 5 to 15 parts of zinc-free vulcanizing accelerators thereon, wherein 5 to 15 parts of zinc-free vulcanizing accelerators are the parts of other components in the masterbatch type accelerator except rubber, and the rubber in the masterbatch type accelerator is calculated within 100 parts of rubber.
[0055] In some typical embodiments of the present application, in order to further improve the performance of the rubber composition so that the prepared tire can better adapt to harsh working environments, the rubber in the rubber composition is selected from any one or more of natural rubber, polyisoprene rubber, polystyrene-butadiene rubber, latex polystyrene-butadiene rubber and polybutadiene rubber. Preferably, the molecular weight of the rubber is 1,000 to 40 million, more preferably 5,000 to 30 million, and more preferably 10,000 to 8 million.
[0056] In some embodiments of the present application, the filler is selected from any one or more of carbon black and white carbon black. Preferably, the specific surface area of white carbon black is 10 to 500 m 2 / g, more preferably 10 to 300 m 2 / g, more preferably 100 to 300 m 2 / g; preferably, the oil absorption value of white carbon black is 20-350mL / 100g, more preferably 25-300mL / 100g, and further preferably 30-290mL / 100g; wherein, based on 100 parts by weight of rubber, the amount of white carbon black is 0 to 100 parts by weight, preferably 0 to 70 parts by weight. Preferably, the specific surface area of carbon black is 10 to 500m2 / g, more preferably 10 to 300 m 2 / g, more preferably 100 to 300 m 2 Based on 100 parts by weight of the rubber, the amount of carbon black used is 0 to 100 parts by weight, preferably 0 to 70 parts by weight.
[0057] Other additives in the rubber composition include but are not limited to any one or more of oil, antioxidant, coupling agent, activator, antioxidant, heat stabilizer, light stabilizer, flame retardant, dye, pigment, plasticizer, softener, processing aid, vulcanizer and accelerator. Those skilled in the art can add corresponding additives according to the specific use environment or requirements of the rubber composition and achieve the expected function. This application has no special restrictions on the above other additives. The dosage of other additives is conventional dosage, or adjusted according to the requirements of actual conditions.
[0058] In some embodiments of the present application, the coupling agent includes any one or more of bis(triethoxypropylsilane) tetrasulfide and disulfide, 3-thiocyanatopropyl-triethoxysilane, γ-mercaptopropyl-trimethoxysilane, zirconate coupling agent, phthalate coupling agent and nitro coupling agent;
[0059] In some embodiments of the present application, the softener includes any one or more of aromatic oil, tackifying resin and tear-resistant resin, and the amount used is 0 to 20 parts by weight, preferably 0 to 10 parts by weight.
[0060] According to another typical embodiment of the present application, a method for continuously preparing a masterbatch using any of the above-mentioned rubber compositions is provided, the method comprising: step S1, mixing a filler, a zinc-free vulcanizing agent, other additives, a rubber and a second solvent, and forming a mixture by stirring; step S2, performing solvent separation on the mixture to obtain a masterbatch.
[0061] The above-mentioned continuous method for preparing a masterbatch not only has a simple preparation process, continuous and efficient, but also has superior processing performance and mechanical properties. Moreover, since the method uses the above-mentioned rubber composition as a raw material and adopts a zinc-free vulcanization accelerator, it can achieve zinc-free emissions and is environmentally friendly. Moreover, the vulcanization accelerator can enable the above-mentioned rubber composition to obtain a cross-linking density close to that of a zinc-containing rubber composition without zinc, and rubber properties such as hardness, tensile stress and hysteresis. The masterbatch prepared by the above-mentioned method has excellent tensile and tearing properties, can adapt to harsh working environments, and is particularly suitable for the preparation of heavy-duty tires.
[0062] The second solvent can be selected from the prior art and can be a benign solvent for rubber. For example, the second solvent can be selected from any one or more of aliphatic hydrocarbon solvents, aromatic hydrocarbon solvents, chlorinated hydrocarbon solvents, ketone solvents, ether solvents and ester solvents. Among them, aliphatic hydrocarbon solvents include but are not limited to various solvent gasoline, cycloalkanes and substituted cycloalkanes, and normal alkanes; aromatic hydrocarbon solvents include but are not limited to benzene, toluene, xylene and styrene; chlorinated hydrocarbon solvents include but are not limited to dichloromethane, chloroform, carbon tetrachloride, dichloroethane, chlorobenzene, tetrachloroethylene, and chlorotoluene.
[0063] In some preferred embodiments of the present application, step S1 includes mixing rubber and a second solvent to prepare a rubber solution, and then mixing it with a filler, a zinc-free vulcanizing agent, and other additives. Dissolving the rubber in the solvent first can make the rubber and other components mix more evenly; preferably, the concentration of rubber in the rubber solution is 1% by weight to 60% by weight, more preferably 5% by weight to 40% by weight, and more preferably 10% by weight to 30% by weight, which is beneficial to improving the preparation efficiency of the masterbatch and product performance, and reducing energy consumption.
[0064] The mixture obtained in step S1 can be immediately transferred to the next step, or can be placed for a certain period of time and heated or not during the placement. When heated, the temperature is 10° C. to 200° C. When the heating temperature is higher than the boiling point of the solvent, the heating needs to be carried out in a pressure vessel.
[0065] The above-mentioned method of solvent separation can be selected from the prior art. In some embodiments of the present application, solvent separation includes any one of evaporation method, low-pressure vacuum drying method, heating method, spray drying method, expansion drying method and flash evaporation method. The specific process parameters of solvent separation using the above-mentioned method can refer to the prior art, and the present application has no particular restrictions.
[0066] In some embodiments of the present application, solvent separation is performed by evaporation, and evaporation is performed using an oven or a drying plate. In some embodiments of the present application, solvent separation is performed by spray drying, and the atomization method is centrifugal atomization, pressure atomization or two-fluid atomization. In some embodiments of the present application, solvent separation is performed by expansion drying, wherein the expansion drying method is to heat first and then suddenly release the pressure. In some embodiments of the present application, solvent separation adopts flash evaporation, which can be at least one of normal pressure flash evaporation or reduced pressure flash evaporation, and the flash evaporation order is 1-3 levels. In some embodiments of the present application, solvent separation adopts low-pressure vacuum drying method, specifically volatilizing solvent or suction filtration under vacuum to a pressure lower than one atmosphere, and the pressure can be -0.1MPa to 0, preferably -0.09MPa to 0, and more preferably -0.08MPa to 0. In some embodiments of the present application, the above-mentioned expansion drying is to flash vaporize the solvent through a screw expansion dryer. Preferably, the screw expansion dryer is pushed along the shaft at 0-20MPa, more preferably 1-10MPa, the pitch decreases, friction generates heat, the outlet pressure drops sharply, the rubber strip expands and relaxes, and the solvent in the rubber strip flashes and vaporizes.
[0067] In some embodiments of the present application, in order to further remove the solvent or moisture in the rubber compound, when the solid content in the rubber compound is lower than 98 wt %, after step S2, step S3 is further included to dry the masterbatch, wherein the drying is heating drying and / or mechanical drying.
[0068] In some embodiments of the present application, the above-mentioned heating and drying is drying or air drying.
[0069] In some embodiments of the present application, mechanical drying is performed using an open mill, a kneading mill, an internal mixer, or a screw extruder, and the working temperature of the mechanical drying is 20°C-250°C.
[0070] In step S3, heating drying can be performed first and then mechanical drying, or mechanical drying can be performed first and then heating drying. When mechanical drying is selected, heating drying can be performed simultaneously, and the temperature is 10°C to 250°C; when heating drying is selected, heating can be performed in a gas medium, and the gas medium includes at least one of air, nitrogen, water vapor, and CO2.
[0071] In the process of solvent separation in the above step S2 and / or step S3, the solvent can be recycled and reused, and the recycling method can be selected from the prior art, such as recycling by a condenser and a fractionation tower. The method for recovering the solvent can use any method known in the art, such as recovering the vaporized solvent by surface condensation or direct contact condensation. When the direct condensation contact method is used, the coolant can be water.
[0072] The masterbatch prepared in the above step S2 can also be mixed with other additives, such as oil, antioxidant, protective wax, sulfur, etc., and after vulcanization treatment, a vulcanized rubber can be prepared for the preparation of heavy-duty tires. According to another typical embodiment of the present application, a masterbatch prepared by any of the above methods is provided for use in heavy-duty tires. The application of the above masterbatch in heavy-duty tires can not only adapt well to harsh working environments, but also achieve zinc-free emissions and be environmentally friendly.
[0073] The beneficial effects that can be achieved by the present application will be further illustrated below in combination with embodiments and comparative examples.
[0074] The specific sources of the materials used in the examples and comparative examples of the present application are as follows:
[0075] Styrene butadiene rubber, ESBR1502, Taiwan Rubber Corporation;
[0076] Natural rubber (NR), STR20#, standard rubber;
[0077] Carbon black: N115, Shanghai Cabot Co., Ltd.; specific surface area 137m 2 / g, oil absorption value 113mL / 100g;
[0078] Carbon black: N220, Shanghai Cabot Co., Ltd.; specific surface area 114m 2 / g, oil absorption value 114mL / 100g;
[0079] Carbon black: N330, Shanghai Cabot Co., Ltd.; specific surface area 78m 2 / g, oil absorption value 102mL / 100g;
[0080] White carbon black: 165MP, Quecheng Silicon Chemical Co., Ltd.; specific surface area 179m 2 / g, oil absorption value 245mL / 100g;
[0081] White carbon black: 115MP, Quecheng Silicon Chemical Co., Ltd.; specific surface area 125m 2 / g, oil absorption value 250mL / 100g;
[0082] Stearic acid, a product of Tyco Brown Chemical (Zhangjiagang) Co., Ltd.;
[0083] Protective wax, a product of Qingdao Jinxian Chemical Co., Ltd.;
[0084] Antioxidant RD, a product of Sinopec Nanjing Chemical Industry Co., Ltd.;
[0085] Antioxidant 4020, a product of Jiangsu Shengao Chemical Technology Co., Ltd.;
[0086] Accelerator CZ, a product of Shandong Shangshun Chemical Co., Ltd.;
[0087] Accelerator DZ, a product of Shandong Shangshun Chemical Co., Ltd.;
[0088] Accelerator DM, a product of Shandong Shangshun Chemical Co., Ltd.;
[0089] Accelerator M, a product of Shandong Shangshun Chemical Co., Ltd.;
[0090] Accelerator NS, a product of Shandong Shangshun Chemical Co., Ltd.;
[0091] Sulfur, a product of Liaoning Chaoyang Tianming Industry and Trade Co., Ltd.;
[0092] Silane coupling agent, Si69, Nanjing Shuguang Silane Chemical Co., Ltd.;
[0093] Comparative Example 1-1
[0094] In an internal mixer, 40 parts of carbon black N220, 20 parts of white carbon black 165MP, and 2 parts of Si69 were added to 80 parts of natural rubber and 20 parts of styrene-butadiene rubber for mixing. After mixing for a period of time, 4 parts of aromatic oil, 4 parts of zinc oxide, 2 parts of stearic acid, 2 parts of antioxidant 4020, 1 part of antioxidant RD, and 1 part of protective wax were added. After the mixed rubber was allowed to stand for 8 hours, 1 part of accelerator CZ and 1.2 parts of sulfur were added to the internal mixer. After the mixed rubber was allowed to stand for 8 hours, it was vulcanized at 150°C for 40 minutes using a flat vulcanizer to obtain dry vulcanized rubber a.
[0095] Comparative Example 1-2
[0096] 40 parts of carbon black N220, 20 parts of white carbon black 165MP and 2 parts of Si69 were added to 80 parts of natural rubber and 20 parts of styrene-butadiene rubber in n-hexane solution and mixed, then continuously injected into the reactor to separate the solvent and dried to obtain masterbatch A. After masterbatch A was added to the internal mixer evenly, 4 parts of aromatic oil, 4 parts of zinc oxide, 2 parts of stearic acid, 2 parts of antioxidant 4020, 1 part of antioxidant RD and 1 part of protective wax were added. After the mixed rubber was allowed to stand for 8 hours, 1 part of accelerator CZ and 1.2 parts of sulfur were added to the internal mixer. After the mixed rubber was allowed to stand for 8 hours, it was vulcanized at 150°C for 40 minutes using a flat vulcanizer to obtain a continuous prepared vulcanized rubber aa.
[0097] Example 1
[0098] Preparation of zinc-free vulcanizing accelerator:
[0099] 10 phr of stearic acid, 12.5 phr of antioxidant 4020, and 11.5 phr of vulcanization accelerator CZ were mixed in xylene and pre-reacted at 130° C. for 40 min to obtain a zinc-free vulcanization accelerator;
[0100] Take 1 / 10 of the above zinc-free vulcanizing agent, 40 parts of carbon black N220, 20 parts of white carbon black 165MP, and 2 parts of Si69, add them to 80 parts of natural rubber and 20 parts of styrene-butadiene rubber in n-hexane solution, mix them, continuously inject them into the reactor to separate the solvent, and dry them to obtain masterbatch A. After adding masterbatch A to the internal mixer evenly, add 4 parts of aromatic oil, 1 part of antioxidant RD, and 1 part of protective wax. After the mixed rubber is left for 8 hours, add 1.2 parts of sulfur to the internal mixer. After the mixed rubber is left for 8 hours, vulcanize it at 150°C for 40 minutes using a flat vulcanizer to obtain a continuously prepared vulcanized rubber A.
[0101] The vulcanized rubbers prepared in the above examples and comparative examples were tested according to the following method. The test results are listed in Table 1.
[0102] Determine the vulcanization characteristics of the rubber compound in accordance with GB / T 16584-1996 Determination of vulcanization characteristics of rubber using a rotorless vulcanizer;
[0103] Determine the physical properties of the rubber compound (tensile strength, elongation at break) in accordance with GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber;
[0104] Determine the hardness of the rubber compound in accordance with GB / T 531.1-2008 Test method for indentation hardness of vulcanized rubber or thermoplastic rubber Part 1: Shore hardness method (Shore hardness)
[0105] According to GB / T 9870.1-2006 Determination of dynamic properties of vulcanized rubber or thermoplastic rubber Part 1: General, the dynamic properties of the rubber compound were determined using a rotational rheometer.
[0106] The filler dispersion grade is determined according to GB / T 6030-2006 Rapid comparative method for the evaluation of carbon black and carbon black / silica dispersion in rubber.
[0107] Table 1
[0108]
[0109] By comparing the physical and dynamic properties of the tread rubber obtained by the continuous preparation process and the dry preparation process in Example 1 and Comparative Examples 1-1 and 1-2, it can be seen that under the same formula, after the continuous preparation process is applied, the dispersion degree of the filler in the rubber is improved, the tensile properties of the vulcanized rubber are excellent, the high-temperature heat generation is reduced, and the DIN wear is significantly improved. Further, the present application obtains performance close to that of the rubber compound with zinc oxide added by adding a zinc-free vulcanizing aid, and the vulcanized rubber A obtained in Example 1 is used for the tread of heavy-duty tires. The zinc content in the rubber compound is determined according to "SN / T 2945-2011 Determination of lead, cadmium, chromium, copper, manganese and zinc content in rubber and its products by inductively coupled plasma atomic emission spectrometry", proving that there is no zinc emission.
[0110] Embodiments 2 to 5
[0111] The difference from Example 1 is that the zinc-free vulcanization accelerator uses a different antioxidant, and the rubber and filler components in the continuous preparation process are different. See Table 2 for the rubber formula. Apart from this, the preparation methods of the zinc-free vulcanization accelerator and the vulcanized rubber are the same as those in Example 1.
[0112] Comparative Examples 2 to 5
[0113] Comparative Examples 2 to 5 were prepared based on the same rubber compound formula as the continuous vulcanized rubber, and their specific formulas are shown in Table 3. The preparation process of the dry vulcanized rubber of Comparative Examples 2 to 5 is the same as that of Comparative Example 1-1.
[0114] Table 2
[0115]
[0116] Table 3
[0117]
[0118]
[0119] Antioxidants used in Table 2 and Table 3 For self-preparation.
[0120] The above examples and comparative examples were tested in the same manner as Example 1. The test results are shown in Tables 4 and 5 below.
[0121] Table 4
[0122]
[0123] Table 5
[0124]
[0125] It can be seen from the test results in Table 4 and Table 5 that under the same formula, after applying the continuous preparation process, the dispersion of fillers in rubber is improved, the tensile properties of the vulcanized rubber are excellent, and the heat generation at high temperature is reduced.
[0126] The vulcanized rubber obtained in Examples 2-5 is used for the preparation of heavy-load tires, such as jumbo tires, engineering tires, mining truck tires, all-steel mining tires, and all-terrain crane tires. After testing, no zinc emission is found.
[0127] In addition, the tire wear chips of Examples 2-5 were subjected to extraction experiments, and the extracts were subjected to HRMS analysis, which confirmed that the self-synthesized environmentally friendly antioxidant did not produce highly toxic quinone compounds. Toxicity testing of the extracts confirmed that the environmentally friendly antioxidants were less toxic to zebrafish and coho salmon than the commercial antioxidant 4020 (6PPD), and were environmentally friendly.
[0128] From the above description, it can be seen that the above embodiment of the present invention achieves the following technical effects: the rubber composition adopts a zinc-free vulcanization accelerator, which reacts the antioxidant and the vulcanization system medicine under the catalytic action of stearic acid to generate an active intermediate, which has the effect of promoting vulcanization and plays the role of an early activation accelerator, so that the active intermediate can replace the role of zinc oxide. The rubber composition does not contain zinc element, can achieve zinc-free emission, and is environmentally friendly; and the vulcanization accelerator can enable the above rubber composition to obtain a crosslinking density close to that of the zinc-containing rubber composition without zinc, and rubber properties such as hardness, tensile stress and hysteresis, especially suitable for the preparation of heavy-duty tires, with excellent tensile and tearing properties, and can adapt to harsh working environments.
[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A rubber composition, characterized in that: In parts by weight, the rubber composition comprises: 100 parts of rubber, 30 to 100 parts of filler, 5 to 15 parts of zinc-free vulcanizing accelerator and 5 to 30 parts of other accelerators; wherein: The zinc-free vulcanization aid is prepared by pre-reacting an antioxidant with a vulcanization system drug under the action of a catalyst, and the catalyst includes stearic acid.
2. The rubber composition according to claim 1, characterized in that The reaction temperature of the pre-reaction is 100-190°C, and the reaction time is 1min-120min; the preferred reaction temperature is 110-170°C, and the reaction time is 5min-50min; Preferably, 0.5 to 15 phr of stearic acid, 0.5 to 15 phr of antioxidant, and 0.5 to 15 phr of vulcanization system chemicals are added to the pre-reaction; Preferably, the pre-reaction further adds a first solvent, wherein the first solvent is any one or more of butanol, octanol, N-methylpyrrolidone, octane, nonane, decane, toluene, and xylene; Optionally, the catalyst further comprises 1 to 10 phr of zinc oxide, and after the pre-reaction is completed, the zinc oxide is filtered out.
3. The rubber composition according to claim 2, characterized in that The vulcanization system chemicals include any one or more of a vulcanizer and an accelerator, and the accelerator includes any one or more of a sulfonamide vulcanization accelerator, a sulfenamide vulcanization accelerator, and a thiazole vulcanization accelerator. Preferably, the accelerator is selected from any one or more of CZ, DZ, DM, M, and NS; And / or, the antioxidant is a p-phenylenediamine antioxidant, Preferably, the antioxidant is selected from any one or more of 4020 (6PPD), 4010NA (IPPD) and 7PPD; Preferably, the antioxidant is a compound having a structure of Formula I: In Formula I, R 1 Selected from C1-C 18 Chain hydrocarbon groups, C3-C 18 Alicyclic hydrocarbon or C6-C 18 The aromatic hydrocarbon group, R 2 , R 3 , R 4 , R 5 Selected from C1-C 18 The chain hydrocarbon group, R 2 With R 3 or R 4 With R 5 They can also form aliphatic rings separately or simultaneously, R 6 Selected from H, C1-C 18 Chain hydrocarbon groups, C3-C 18 Alicyclic hydrocarbon or C6-C 18 An aromatic hydrocarbon group; x = 0 or 1, y = 0 or 1, z=0 or 1, w=0 or 1, and at least one of x and w is 1, and at least one of y and z is 1.
4. The rubber composition according to claim 1, characterized in that The filler is selected from any one or more of carbon black and white carbon black; Preferably, the specific surface area of the white carbon black is 10 to 500 m 2 / g, more preferably 10 to 300 m 2 / g, more preferably 100 to 300 m 2 / g; Preferably, the oil absorption value of the white carbon black is 20 to 350 mL / 100 g, more preferably 25 to 300 mL / 100 g, and further preferably 30 to 290 mL / 100 g; Preferably, the specific surface area of the carbon black is 10 to 500 m 2 / g, more preferably 10 to 300 m 2 / g, more preferably 100 to 300 m 2 / g.
5. The rubber composition according to claim 1, characterized in that The rubber is selected from any one or more of natural rubber, polyisoprene rubber, molten polystyrene-butadiene rubber, latex polystyrene-butadiene rubber and polybutadiene rubber; Preferably, the molecular weight of the rubber is 1,000 to 40 million, more preferably 5,000 to 30 million, and even more preferably 10,000 to 8 million.
6. The rubber composition according to claim 1, characterized in that The other additives include any one or more of oil, antioxidant, coupling agent, activator, antioxidant, heat stabilizer, light stabilizer, flame retardant, dye, pigment, plasticizer, softener, processing aid, vulcanizer and accelerator; Preferably, the coupling agent includes any one or more of bis(triethoxypropylsilane)tetrasulfide and disulfide, 3-thiocyanatopropyl-triethoxysilane, γ-mercaptopropyl-trimethoxysilane, zirconate coupling agent, phthalate coupling agent and nitro coupling agent; Preferably, the softener includes any one or more of aromatic oil, tackifying resin and anti-tear resin.
7. A method for continuously preparing a masterbatch using the rubber composition according to any one of claims 1 to 6, characterized in that: The method comprises: Step S1, mixing a filler, a zinc-free vulcanizing agent, other additives, rubber and a second solvent, and forming a mixture by stirring; Step S2, separating the solvent from the mixture to obtain a masterbatch.
8. The method according to claim 7, characterized in that The solvent separation includes any one of evaporation, low pressure vacuum drying, heating, spray drying, expansion drying and flash evaporation; Preferably, after step S2, the method further comprises step S3 of drying the masterbatch, wherein the drying is performed by heating and / or mechanical drying.
9. The method according to claim 7 or 8, characterized in that: The second solvent is selected from any one or more of aliphatic hydrocarbon solvents, aromatic hydrocarbon solvents, chlorinated hydrocarbon solvents, ketone solvents, ether solvents and ester solvents; Preferably, the step S1 comprises mixing the rubber and a second solvent to prepare a rubber solution, and then mixing the rubber solution with the filler, the zinc-free vulcanizing agent, and other additives; Preferably, the concentration of rubber in the rubber solution is 1% to 60% by weight, more preferably 5% to 40% by weight, and even more preferably 10% to 30% by weight.
10. Use of the masterbatch prepared by the method according to any one of claims 7 to 9 in heavy-load tires.
Citation Information
Patent Citations
Method for preparing white carbon black / solution polymerized styrene-butadiene rubber masterbatch by wet process
CN106750389A
Room-temperature sulfurization preparation method for carbon nanotube-filled natural rubber composite material
CN103554563A
Anti-ageing rubber promoter
CN103865113A
Preparation method of low temperature resistant acrylate rubber
CN108084328A
Low temperature resistant nitrile rubber and preparation method thereof
CN110157058A